The impact of information sharing on the quality of decision-making: From the point of view of employees in Jordanian private hospitals - Fahd Alduais; Atef Raoush; Abeer Samara; Khaled Sartawi (Cogent Business & Management)
This paper examines how information sharing impacts the quality of decision-making in Jordanian private hospitals from the point of view of employees. It involved a structured questionnaire, which consisted of demographic data, information sharing, and decision-making. The research results suggest that sharing information in both common and unique situations significantly positively influences the decision-making abilities of teams. Merely possessing unique information does not enhance the ability to make decisions; conversely, common information is crucial to facilitate the decision-making process. Participant characteristics have no effect on decision-making quality, especially as team functional diversity continues to rise, with information sharing even less relevant as a result. Our results indicate that participants’ characteristics do not predict whether the discussion of shared information will contribute to decision-making quality. As a practical contribution, our findings recognise the importance of decision teams in information management, encourage flexibility and openness in organisational relations, and assist policymakers, managers, and regulators through training programs that confirm participation is one of the most important components of generating new ideas.